The Impact of the EU’s Generalized System of Preferences Plus Status on Companies and Fiscal Policy of Pakistan: A Case of the Textile Industry - Choudhary Mazhar Hussain (Financial Internet Quarterly)
This paper's main goal is to evaluate the before and after effects of EU’s GSP plus on Pakistani company’s tax payment of textile sector and suggesting the Fiscal policy. In fact, the study address what effect does the Generalized System of Preferences (GSP) plus Status of the EU have on the corporate taxation of Pakistan's textile industry and on tax policy? For that purpose, in this study the regression analysis is used. The data of listed local and international companies are gathered from Pakistan Stock Exchange. The results depict that exporting companies able to increase their profits and pay more corporate tax led to impart in the sustainable economic growth of Pakistan. This study will help out the fiscal policy makers in the development of tax policy for the potential exports sector to EU. Furthermore, assist the financial managers to create a corporate strategy for the multinational firms.